ORTHODOX CURRENCY BOARD AND CURRENCY BOARDS OF THE SECOND GENERATION: OPERATIONAL ASPECTS (Heritage, 2021)
In this paper, a survey was conducted in five countries, Bosnia and Herzegovina, Bulgaria, Estonia, Lithuania and Hong Kong, whose monetary systems apply the currency board as a monetary policy regime. The research was conducted in the period from 1995 to 2018. The research is based on the use and analysis of central bank laws for each of these countries. The key points analyzed in each law are the legal basis and monetary operations. On the basis of exploratory research and comparative analysis of key points, it was found that significant differences appear in the mentioned monetary systems, which function in the currency board. The differences arise from the legal bases in the operational aspects of the application of monetary operations. Precisely on the basis of these differences, which are the facts defined in certain laws, the conclusion is that today we can rightfully talk about two types of currency boards, ie orthodox currency boards and second generation currency boards.
Keywords: Currency Board, Central Bank, Monetary Operations, Fixed Exchange Rate, Convertibility